MENELAAH PENGARUH PENDIDIKAN ANAK USIA DINI TERHADAP PERKEMBANGAN ANAK - Nur Ilmi Khairani; Zainal Efendi Hasibuan (Yayasan Baitul Hikmah al-Zain, 2025)
This study aims to identify the problems faced by early childhood in their cognitive development. Where parents must know at what age their children can determine education so that children can develop according to their cognitive development. The method used in this study is a qualitative case study. Education in early childhood basically includes all the efforts and actions made by educators and parents during the care and education of children. Before children are put into school, people must know the period of child development so that there are no gaps in the future.